Pelaksanaan Peraturan Daerah Kabupaten Rokan Hulu Nomor 6 Tahun 2011 Tentang Retribusi Perizinan (Studi Retribusi Izin Mendirikan Bangunan) - Ummi Muslimah; Ahmad Yuza (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2020)
This study aims to determine how the implementation of Rokan Hulu District Regulation Number 6 of 2011 concerning Certain Permits Retribution (Study of Building Permits Retribution) and to determine the obstacles. The indicators used in this research are communication, resources, disposition and bureaucratic structure. This type of research, which is located in Rokan Hulu Regency, uses descriptive types and qualitative methods. There are two types of data used in this study, namely primary data collected by interview techniques and secondary data collected by observation and documentation techniques. The informants in the study consisted of the Head of the One Stop IntegratedService Investment Service, Secretary of the Civil Service Police Unit and Fire Service of Rokan Hulu Regency, Head of Licensing and Non-Licensing A, Head of Licensing and Non-Licensing Section A/II, Staff of the Licensing and Non-Licensing Section A/II, Public. Data analysis in this research is inductive, data collected through data collection techniques will be described objectively in accordance with the factual conditions in the field. Based on the data analysistechnique, the research supposition is "Implementation of Rokan Hulu District Regulation Number 6 Year 2011 concerning Certain Permits Retribution (Building Construction Permits) is not implemented". Meanwhile the obstacles inimplementing this policy are limited availability of budget, still weak human resources of the leaders of the Investment and One Stop Services of Rokan Hulu Regency, which have an effect on the lack of dedication in increasing income from building permits retribution, still weak human resources. Rokan Hulu Regency community, which resulted in a lack of public awareness of the importance of building permits, the available facilities were inadequate. Meanwhile, thesuggestions recommended by researchers that need to be considered need to be maximized coordination among Regional Apparatus Organizations, increase socialization to the community, and need to carry out regular and continuous supervision, as well as the need for additional implementor incentives and additional facilities for adequate facilities andinfrastructure.